`What it takes`: perceptions of mental toughness and its development in an English Premier League Soccer Academy - Cook, C.; Crust, L.; Littlewood, M.; Nesti, M.; Allen-Collinson, J. (Qualitative Research in Sport, Exercise and Health, 2014)
The purpose of this qualitative study was to undertake an in-depth exploration of coaches` and support staff perceptions regarding mental toughness and its development in the pressurised and distinctive sub-cultural milieu of an English Premier League (EPL) Soccer Academy. Semi-structured interviews were conducted with eight key staff responsible for a range of different roles in the development of young players. From the analysis, four general dimensions emerged as salient to mental toughness: competitiveness with self and others, mindset, resilience and personal responsibility. To enhance mental toughness, coaches sought to foster in the young players two key characteristics: independence and resourcefulness, via a challenging but supportive learning environment. Importantly, attention to the psychological development of young players was reported to be inadequately addressed in comparison with other aspects of performance such as technical skill or physical conditioning. Although mental toughness was acknowledged to be a crucial factor in securing a professional contract in the EPL, coaches reported a relative lack of knowledge about effectively nurturing this quality in players.